Влияние ионной имплантации на напряженно – деформированное состояние режущей части инструмента - Ласуков, А.А.; Моховиков, А.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The given article considers the changes in the cutting wedge deformation mode while machining caused by ion implantation of surface layer of the face of tool. The last influences the machining process characteristics, improving the tool functionality.